IPhone : the Missing Manual. - Pogue, David (Missing manual., 2011)
With the iOS5 software and the new iPhone 4S device, Apple has another world-class hit on its hands. This sleek, highly refined pocket computer comes with everything--cellphone, iPod, Internet, camcorder--except a printed manual. Fortunately, David Pogue is back with the latest edition of his witty, crystal-clear, colorful guide: the world's most popular iPhone book. Use it as a phone. Learn the basics as well as time-saving tricks and tips for contact searching by voice, texting, and more. Manage hour stuff in the cloud. Sync and back up your contacts and media across all of your devices with iCl.